Methodological and economic evaluations of seven survey modes applied to health service research - Kritsanee Saramunee (2018)
© 2016 Royal Pharmaceutical Society. Objective: To evaluate methodological outcomes and cost-effectiveness of seven survey modes, using a study of general public views towards pharmacy public health services. Methods: A cross-sectional, paper-based survey was conducted in North West England among people aged ≥18 years, using two approaches. Three interviewer-assisted modes were street, door-to-door and telephone. Four self-completion modes were single- and double-mailing to residential addresses, surveys sent to public/private business by post (postal-business) and questionnaires dropped-off at venues (drop-off). The study compared response rates, demographics and two domains ((a) actual use of and (b) willingness to use pharmacy public health services) between modes. Incremental cost-effectiveness ratios of different modes were assessed against the single-mailing. Key findings: Response rate varied between 5.1% (postal-business) and 34.5% (street). Respondent age, education, employment, socioeconomic and deprivation status varied between different modes. Results for domain (a) were similar for all modes. Interviewer-assisted modes resulted in more positive views on willingness to use advisory services (P < 0.05). The drop-off mode saved £45.92 (US$72.55) per 1% increase in response rate compared to single-mailing, while interviewer-assisted and double-mailing were more costly. At higher response rates, cost-savings by the drop-off mode diminished, but for other survey modes, additional costs decreased. Conclusion: Drop-off mode is cost-effective compared to the standard single-mailing, but selection bias is possible. Street surveys are also an efficient method, but may carry a higher risk of obsequiousness bias. Mixed-modes surveys may reach wider sectors of the population. The similarity in use of services suggests all survey modes reach members of the public relevant to pharmacy researchers. JPHSR